Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s40580-020-00244-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intracellular transition metal ion level with a pH-sensitive inorganic nanocluster to improve therapeutic angiogenesis by enriching conditioned medium retrieved from human adipose derived stem cells

Abstract: Cell therapy based on human adipose derived stem cells (hADSCs) is a known potential therapeutic approach to induce angiogenesis in ischemic diseases. However, the therapeutic efficacy of direct hADSC injection is limited by a low cell viability and poor cell engraftment after administration. To improve the outcomes of this kind of approach, various types of nanoparticles have been utilized to improve the therapeutic efficacy of hADSC transplantation. Despite their advantages, the adverse effects of nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The delivery of metal (Fe) ions to enhance hMSC-based wound healing has been achieved by engineered bioreducible ETIN. Fe ions could be released within the cells in response to the low-pH conditions in endosomes. ,, To strongly confirm those mechanisms, Kim and co-workers demonstrated that ps-TNCs can improve the angiogenic efficacy of hADSCs by controlling the intracellular transition ion level, which has also been applied to ischemic lesions the CM derived from psTNC-treated hADSCs as shown in Figure a–c …”
Section: Enm-based Nano–bio Reactions For Stem Cell Therapymentioning
confidence: 83%
See 1 more Smart Citation
“…The delivery of metal (Fe) ions to enhance hMSC-based wound healing has been achieved by engineered bioreducible ETIN. Fe ions could be released within the cells in response to the low-pH conditions in endosomes. ,, To strongly confirm those mechanisms, Kim and co-workers demonstrated that ps-TNCs can improve the angiogenic efficacy of hADSCs by controlling the intracellular transition ion level, which has also been applied to ischemic lesions the CM derived from psTNC-treated hADSCs as shown in Figure a–c …”
Section: Enm-based Nano–bio Reactions For Stem Cell Therapymentioning
confidence: 83%
“…125,126,128 To strongly confirm those mechanisms, Kim and co-workers demonstrated that ps-TNCs can improve the angiogenic efficacy of hADSCs by controlling the intracellular transition ion level, which has also been applied to ischemic lesions the CM derived from psTNC-treated hADSCs as shown in Figure 8a−c. 141 Despite the mechanisms mentioned above, however, the low viability of hMSCs following transplantation has been identified as the problem. Park et al addressed this challenge by developing Fe ion-releasing gold NPs for advanced tumortargeted photothermal therapy using hMSCs where Fe ions are released in hMSCs under low pH conditions.…”
Section: Ion Releasementioning
confidence: 99%
“…2 ) [ 58 ]. Iron-ion-induced ROS also upregulates hypoxia inducible factor-1α (HIF-1α) expression in MSCs, which in turn, can elevate MSC secretion of paracrine factors like VEGF (supports angiogenesis during wound repair) and basic fibroblast growth factor (bFGF) (supports angiogenesis) [ 59 ]. Essentially, HIF-1α acts as a transcription factor, binds to VEGF promoter and induces VEGF expression [ 56 , 60 , 61 ].…”
Section: Msc Tropism Towards Tumour/inflammation and Contextual Ionp-induced Msc Alterationsmentioning
confidence: 99%
“…TNC itself is continuously up-regulated during the wound repair process. A large number of experiments have established that TNC exerts pro-angiogenic effects [ 9 , 10 , 11 , 12 ]. However, angiogenesis did not increase significantly during the inflammatory phase of tissue injury [ 13 , 14 ], although TNC levels gradually increased.…”
Section: Introductionmentioning
confidence: 99%